Creating a sense of place in school environments : how young children construct place attachment - Rieh, Sun-Young (New York, NY : Routledge, 2020)
"Creating a Sense of Place in School Environments guides its readers to the characteristics that tend to generate a sense of place through children's vivid descriptions of their school and provides a body of critical information that can be employed to design a better school environment that can imprint cherished childhood memories. The childhood school environment calls for special attention regarding the sense of place it creates. The sense of place in childhood both affects children's current quality of life and frames their lasting world view. It is well known that children's cognitive development is closely related to their place attachment to their surroundings, and that children's adaptation to a given environment depends on how such place attachment can be created. Therefore, it is natural that people's identity in the world is the accumulation of their experience of place while in childhood. Cross checking between the imprint of adults' memories of places in school and children's current "lived experience" of their favorite school place confirmed that certain spatial configurations, which author herein refers to as "place generators" can generate positive attributes of physical settings that construct a sense of place and last as lifelong memories. An ideal read for academics, students, and professionals"--
7.2 Sense of Place in Schools Sharing with Community: Case of Dutch Brede Schools -- Awareness of Shared Space: Confidence on School Environment -- Psychological restriction -- Notes -- 8 Conclusion: Toward a "Sense of Place" in School Environments -- References -- Index
OCLC-licensed vendor bibliographic record.
Keywords: School environment -- Psychological aspects; School children -- Psychology; Place attachment; ARCHITECTURE / General; ARCHITECTURE / Criticism; ARCHITECTURE / Design & Drafting